The Influence of User Reviews, Digital Customer Service Quality, and Social Media Promotion on Generation Z's Interest in Gold Investment (BSI E-Mas) - Jihan Khairani; Mutia Sumarni; Friska Anggi Siregar (Universitas Ibn Khladun Bogor, 2026)
This study aims to analyze the influence of user reviews, digital customer service quality, and social media promotions on gold investment interest (e-gold BSI) in Generation Z. The study uses a quantitative approach with a causal design. The research sample consisted of 100 respondents selected using a purposive sampling technique. The analytical method used is descriptive analysis and multiple linear regression with the help of SPSS. The results of the study indicate that simultaneously user reviews, digital customer service quality, and social media promotions have a significant effect on gold investment interest (e-gold BSI) in Generation Z. This is proven by the results of the F test with a significance value of 0.000 <0.05 and a calculated F value of 169.364. Partially, user reviews have a positive and significant effect on investment interest with a significance value of 0.005 <0.05 and a calculated t of 2.898 > t table 1.661. The social media promotion variable also had a positive and significant effect, with a significance value of 0.000 < 0.05 and a calculated t-value of 5.756 > t-table value of 1.661. Meanwhile, the quality of digital customer service did not significantly influence gold investment interest, with a significance value of 0.250 > 0.05 and a calculated t-value of 1.158 < t-table value of 1.661. The Adjusted R-square value of 0.836 indicates that 83.6% of the variation in gold investment interest can be explained by the three independent variables in this study.